2018
DOI: 10.4103/jnrp.jnrp_38_18
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Clinical Importance of Skull Base Fractures in Adult Patients with Traumatic Brain Injury

Abstract: Aims and Objectives:Basal skull fracture (BSF) is rare in head injury (HI) patients and occasionally goes unnoticed which may lead to cerebrospinal fluid (CSF) fistula. With changing trends in HI, there is a need to reassess incidence and pattern of BSF pattern, CSF leak, meningitis, and management protocol, especially in this part of the world where detailed literature is lacking.Subjects and Methods:We closely followed adult patients admitted with BSF in our institute between January 2013 and December 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
0
16
1
5
Order By: Relevance
“…Notably, these cohort characteristics are consistent with those in previous studies. 4,6,8 A striking contrast between these studies and ours is that while the former have consistently shown vehicle-related accidents to be the most common aetiology of traumatic head injuries, our study found assault to be the highest cause, accounting for 46% (98/210) of all cases of traumatic head injury evaluated. This finding implies that there were high levels of interpersonal violence in this study population, despite a survey by Statistics South Africa reporting a moderate decline in assault cases between 2013 and 2017.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Notably, these cohort characteristics are consistent with those in previous studies. 4,6,8 A striking contrast between these studies and ours is that while the former have consistently shown vehicle-related accidents to be the most common aetiology of traumatic head injuries, our study found assault to be the highest cause, accounting for 46% (98/210) of all cases of traumatic head injury evaluated. This finding implies that there were high levels of interpersonal violence in this study population, despite a survey by Statistics South Africa reporting a moderate decline in assault cases between 2013 and 2017.…”
Section: Discussioncontrasting
confidence: 97%
“…The predominance of MCF fractures is thought to be because of the presence of neurovascular foramina (which are presumed to be points of structural weakness) and thin bones in the MCF, which render it susceptible to fractures in comparison with the anterior and posterior compartments. 4,6 Furthermore, the site of impact in the case of head injury tends to be from the sides or front. 2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,16 Although CSF leaks are known to occur after skull fractures in a minority of cases, precise risk estimates in the pediatric population are extremely limited, 1,16 and our current understanding derives from single-institution studies of skull base injuries. 13,20,24,27,28 In this study, we used the MarketScan database between 2007 and 2015 to assemble a large cohort of pediatric patients with skull fractures. We examined the characteristics and clinical outcomes of pediatric skull fracture patients with and without CSF leaks, and we longitudinally assessed the healthcare costs associated with the care of these patients.…”
mentioning
confidence: 99%